Typification of 25 names in Inula (Inuleae, Asteraceae), and a new combination in Pentanema - Gutiérrez-Larruscain, David; Santos-Vicente, M.; Martínez-Ortega, M. Montserrat; Rico, E. (Phytotaxa, 2019)
23 new typifications of names in Inula—four of them being basyonyms of currently accepted species under Pentanema (P. helenioides, P. helveticum, P. langeanum and P. maletii)—, and 2 new typifications of names in Aster are provided in this paper. 18 new lectotypes, 7 neotypes and one epitype are designated. Additional materials relevant to typification and protologue citation are indicated in each case. Finally, a new combination in Pentanema (P. squarrosum) is proposed.